Beyond waste: new sustainable fillers from fly ashes stabilization, obtained by low cost raw materials - Rodella, N. (Heliyon, 2016)
A sustainable economy can be achieved only by assessing processes finalized to optimize the use of resources. Waste can be a relevant source of energy thanks to energy-from-waste processes. Concerns regarding the toxic fly ashes can be solved by transforming them into resource as recycled materials. The commitment to recycle is driven by the need to conserve natural resources, reduce imports of raw materials, save landfill space and reduce pollution. A new method to stabilize fly ash from Municipal Solid Waste Incinerator (MSWI) at room temperature has been developed thanks to COSMOS-RICE LIFE+ project (www.cosmos-rice.csmt.eu). This process is based on a chemical reaction that occurs properly mixing three waste fly ashes with rice husk ash, an agricultural by-product. COSMOS inert can replace critical raw materials (i.e. silica, fluorspar, clays, bentonite, antimony and alumina) as filler. Moreover the materials employed in the stabilization procedure may be not available in all areas. This paper investigates the possibility of substituting silica fume with corresponding condensed silica fume and to substitute flue-gas desulfurization (FGD) residues with low-cost calcium hydroxide powder. The removal of coal fly ash was also considered. The results will be presented and a possible substitution of the materials to stabilize fly ash will be discussed.